Distribution of mercury‐cycling genes in the Arctic and equatorial Pacific Oceans and their relationship to mercury speciation. (26th August 2019) - Bowman, Katlin L.; Collins, R. Eric; Agather, Alison M.; Lamborg, Carl H.; Hammerschmidt, Chad R.; Kaul, Drishti; Dupont, Christopher L.; Christensen, Geoff A.; Elias, Dwayne A.
Abstract: Humans are exposed to potentially harmful amounts of the neurotoxin monomethylmercury (MMHg) through consumption of marine fish and mammals. However, the pathways of MMHg production and bioaccumulation in the ocean remain elusive. In anaerobic environments, inorganic mercury (Hg) can be methylated to MMHg through an enzymatic pathway involving the hgcAB gene cluster. Recently, hgcA ‐like genes have been discovered in oxygenated marine water, suggesting the hgcAB methylation pathway, or a close analog, may also be relevant in the ocean. Using polymerase chain reaction amplification and shotgun metagenomics, we searched for but did not find the hgcAB gene cluster in Arctic Ocean seawater. However, we detected Hg‐cycling genes from the mer operon (including organomercury lyase, merB ), and hgcA ‐like paralogs (i.e., cdhD ) in Arctic Ocean metagenomes. Our analysis of Hg biogeochemistry and marine microbial genomics suggests that various microorganisms and metabolisms, and not just the hgcAB pathway, are important for Hg methylation in the ocean.